Faust Syndrome: Do negative moral emotions leave marks on employees’ health? --- - Majstorović, Nebojša; Šolak, Radojka (Psihološka istraživanja, 2025)
The paper is aimed at evaluating the incidence of the Faust Syndrome indicators and examining the effects of this syndrome of work relationships on employees’ psycho-physical health mediated by negative moral emotions towards others induced in such relationships. The sample consisted of 611 participants (64.5% women), employed at various positions (83.3% executive), of the average age of 37.13 (SD = 11.94), and the average length of service of 8.09 years (SD = 8.75). In order to measure toxic work relationships in the form of the Faust Syndrome (FS), the Faust Syndrome Questionnaire (FSQ-2) was used to assess five dimensions: Loyalty to the employer, Subversive behaviour, Manipulation of the decision-making system, Ostracism and Negative attitudes towards colleagues. The incidence of negative moral emotions at the workplace scale (SUMO) measured the following negative moral emotions towards others: Anger, Disgust, Rage, Envy, Belittling, Malice, Jealousy and Contempt. The scale of psycho-physical health (SPFZ-1) was used to assess Physical health disorder, Fear and anxiety, Depression reactions, Fatigue and Social behaviour disorder. The results indicate that the Faust Syndrome has a significant effect on the increased expression of negative moral emotions towards co-workers, that these emotions most likely have a significant effect on the employees’ psycho-physical health, as well as that these same emotions act as mediators between toxic work relations and the employees’ health. It is concluded that negative moral emotions towards others, which are probably induced by the Faustian Syndrome, do leave marks on employees’ health.
Keywords: The Faust Syndrome; toxic work relations; negative moral emotions towards others; psycho-physical health; employees